PENYELENGGARAAN PELAYANAN PUBLIK BERDASARKAN ASAS OTONOMI DAERAH PADA KECAMATAN GEDONG TATAAN- KABUPATEN PESAWARAN - Martina Male (Law Faculty of Universitas Bandar Lampung, 2019)
Abstract: The system of government in Indonesia according to the 1945 Constitution, based on the explanation stated that the regions of Indonesia are divided into provincial and provincial regions will also be divided into smaller areas in autonomous regions. In legal politics, the most essential in the implementation of autonomous regional government is the granting of the broadest authority to the regions accompanied by the granting of certain rights and obligations. In the reality in the field, this policy was not implemented in accordance with the provisions of the Act. The lack of optimal public services in serving the people in several regions in Indonesia in various fields, including government agencies, has not yet been able to provide maximum public services, so in this paper will discuss how the efforts made by the Regional Government, especially in Gedong Tataan Subdistrict, Pesawaran District in organizing and improving public services based on its Regional Autonomy Principle. The efforts made in the discussion and solving problems in this study were carried out using a juridical / normative approach and empirical approach. The implementation of public policy based on the principle of regional autonomy in the District of Pesawaran District Gedong Tataan is in accordance with Law Number 23 of 2014 concerning Regional Government and Law Number 25 of 2009 concerning Public Services, but there are technical obstacles such as the distance from public services to one another, less responsive, less informative and lacking coordination in service delivery. Efforts that can be made by the Gedong Tataan District Government in improving the quality of public services are through revitalization, restructuring and deregulation in the field of public services. Suggestions that can be given to the Regional Government, especially in the District of Pesawaran District Gedong Tataan in carrying out public services based on the principle of autonomy are: expected in carrying out the process of implementing public services must be in accordance with Law Number 25 of 2009 concerning Public Services and expected improvement in the quality of behavior and professionalism of the apparatus government, creating public service policies that are not too procedural and convoluted, and improve facilities that support quality services.